Clinical psychologists' attitudes towards the biology and 'new genetics' of intellectual and developmental disabilities: a pilot study using Q‐methodology. Issue 11 (29th February 2016) - Hare, D.J.; Vahey, C.; Walker, S.; Wittkowski, A.
Abstract: Background: The current study investigated how ideas and models from the 'New Genetics' and associated fields of developmental neuroscience and behavioural phenotypes are perceived by clinical psychologists working with people with intellectual and developmental disabilities (IDD). As well as examining the take‐up and influence of such ideas, it also examines barriers, both personal and institutional, to the widespread adoption of such concepts and research findings in services for people with IDD. Methods: A Q‐methodology study was undertaken with 31 qualified and 16 trainee clinical psychologists in the North West of England using a specifically developed 81‐item Q set. Results: Three factors were identified and labelled Integration of social and medical models, Social model of disability is more helpful and Genetic advances in conflict with recognising the value of people with IDD. Conclusion: There was a lack of consensus in clinical psychologists working with people with IDD, with amount and type of professional experience affecting the factor loadings, which may need to be considered in developing clinical applications of genetic IDD research.